Fibroepithelioma of Pinkus in continuity with nodular basal cell carcinoma: A rare presentation - Atul M Dongre; Uday S Khopkar; Yogesh N Kalyanpad; Prachi V Gole (Wolters Kluwer Medknow Publications, 2016)
Fibroepithelioma of Pinkus and nodular basal cell carcinoma (BCC) are different morphological variants of BCC. It is very rare to see both the variants together in a single lesion. Here we report a case of a 56-year-old female who presented with a nodule on the trunk, which on biopsy showed features of both nodular BCC and fibroepithelioma of Pinkus.